Transfer of technology (ToT) document of polyimide binder resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan. N. N.; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhansekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (2009)

Amino-phenol-formaldehyde resins by in-situ generation of catalyst - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Tayal, Rajivkumar; Qureshi, Moham (2010)

Beaded cross linked polymers containing tert-amino functional group moities - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Tayal, Rajivkumar; Qureshi, Moham (2010)

Process for synthesis of beaded cross linked polymers, water-in-oil-in-water emulsions and post functionalisation - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Tayal, Rajivkumar; Qureshi, Moham (2010)

Transfer of technology (ToT) document of ethyl silicate-32 - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of Technology (ToT)/ Technical Documents, 2011)

Transfer of technology (ToT) document of phenol-aniline-formaldehyde (sf-342a) resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of technology (ToT) document, 2011)

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.